Identification of Toxoplasma Gondii Cyst in Ras Chicken as A Potential Infection of Toxoplasmosis - Farisa Al Amin Avin; Soenarnatalina Melaniani (JURNAL KESEHATAN LINGKUNGAN, 2018)
Toxoplasmosis is a zoonotic diseases caused by Toxoplasma gondii,which spread out by cats and it can be found in fowl. It because the fowl swallowing food which had been infected byToxoplasma gondii oocyst. The most consumpted fowl is chicken.The source of data and agriculture information center showed that consumption of chicken was increased about 10,20%. It could be a potential increasement of Toxoplasma gondii infection. The objective of this research was indentificate the infection of  Toxoplasma gondii cyst on ras chicken brain. The type of this research was a descriptive research, observe by examining 30 samples of the ras chicken brain by randomized sampling techniques. Based on research on 30 samples of the ras chicken brain, obtained positive results as much as 2 samples (6.6%) cyst infected of Toxoplasma gondii and others 28 samples of ras chicken brain (93.4%) were not infected with Toxoplasma gondii cysts. Positive results of Toxoplasma gondii can be caused due to maintenance system and cleanliness of chicken coop was much less, so there were carrier vectors contaminate to feed place, so there was a potential infection of Toxoplasmosis.It can be concluded that been 2 samples of chicken brain being infected cyst of Toxoplasma gondii or about 6,6% and there were 28 samples or 93,4% of chicken brain that were not infected by cyst of Toxoplasma gondii. Infection circle of Toxoplasmosis can be avoided by manage maintenance system of chicken and keep the cage cleamliness, also keep the personal hygiene and feeds.